Pengukuran dan Perencanaan Produktivitas Dengan Menggunakan Metode APC (American Produktivity Center) - Cahyadi, Ujang; Taptajani, Dedi Sa'dudin; Miraj, Ahmad Fauzi Saepul (Institut Teknologi Garut, 2025)
PD. Jaya Rasa is a micro, small, and medium enterprise (MSME) in the food industry that produces makaroni cikruh. The issue faced is the fluctuating monthly production, which is inconsistent and fails to meet targets. Therefore, the objective of this study is to measure productivity and analyze improvements across several factors—such as labor, energy, raw materials, and machinery—that contribute to the decline in productivity, in order to utilize company resources more efficiently and effectively. This study uses the American Productivity Center (APC) method to determine productivity, profitability, and price improvement values by accounting for labor, raw materials, energy, and total inputs. To identify the root causes of productivity decline, a Fishbone Diagram is applied. The study finds that the highest productivity index was in energy at 106.367 percent during January, while the lowest was in labor at 91.864 percent in December. The proposed recommendations include monitoring the production process, conducting regular performance evaluation and skill training, and purchasing more modern packaging equipment, such as a sealing machine, to accelerate the packaging process.